Case Report: Uniportal Video-Assisted Thoracoscopic Parenchymal Sparing Secondary Carinal Resection and Reconstruction for the Treatment of Tracheobronchial Mucoepidermoid Carcinoma - Hu, Yan; Chen, Xiaofeng; Ren, Siying; Zeng, Chao; Wang, Li; Xiao, Peng; Yu, Fenglei; Liu, Wenliang (Frontiers in Surgery, 2022)
Surgical resection is currently the mainstay of treatment for tracheobronchial mucoepidermoid carcinoma (TMEC). The parenchymal sparing secondary carinal resection and reconstruction for TMEC under the uniportal thoracoscopic approach has seldomly been reported in the literature. Here, we report a case of a 42-year-old male patient complaining of the incidental finding of a 1.5cm*1.2cm neoplasm at the opening of the right bronchus intermedius and a 5.1cm*3.1cm patchy lesion located at the left upper lobe by chest CT scans in February 2021. This patient successively underwent fiberoptic bronchoscopic biopsy of the bronchial neoplasm and CT-guided biopsy of the left upper lobe lesion. Pathological examination confirmed the diagnosis of the endobronchial mass in the right bronchus intermedius as low-grade mucoepidermoid carcinoma and left upper lobe lesion as tuberculosis. This patient successfully underwent uniportal thoracoscopic parenchymal sparing tumor resection, reconstruction of the secondary carina and lymphadenectomy at our center. Intraoperative frozen section showed no residual cancer at any bronchial stumps. Postoperative pathology indicated that no metastases were seen in any of dissected lymph nodes. The patient recovered well after surgery. After surgery, he received a 9-month course of anti-tuberculosis treatment. He did not complain of any special discomfort and there was no local recurrence at the 9-month postoperative follow-up. Although technical demanding, this case highlights that uniportal video-assisted thoracoscopic parenchymal sparing secondary carinal resection and reconstruction for TMEC is safe and feasible with the preservation of lung function and excellent outcomes.